Understanding the Complexities of Educational Change Resistance Amongst Teachers in Ilorin West Lga, Kwara State - Lasisi, Adekola Kamil; Oreagba, Fatimah (Indonesian Journal of Educational Science and Technology, 2024)
The study was conducted to understand the complexities of educational change resistance of primary school teachers in Ilorin West Local Government Area of Kwara State. The study employed the thematic qualitative design approach. Convenience sampling was used to select ten participants who were willing to participate and could access the online survey interview that was conducted. The instrument used was Educational Change Resistance Interview (ECRI).Data collected was analysed and common themes were identified. The results revealed that educational change is a complex and multifaceted phenomenon that requires a holistic and contextualized understanding of teachers’ perceptions, experiences, and factors that influence their resistance or acceptance. Resistance of educational change can be curbed through compensation, motivation, support and training, communication and involvement.